The Emergence of a More Conventional Reading of the Conventionality Control Doctrine - Paúl, Álvaro (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2019)
The Inter-American Court of Human Rights developed a doctrine called conventionality control. In general terms, this doctrine is somewhat similar to the idea of judicial review of legislation, but applied in a transnational forum. According to the Court, conventionality control would require domestic judges and other bodies of States parties to the American Convention on Human Rights (ACHR) to depart from domestic legislation that runs counter to the ACHR or the Inter-American Court’s interpretation of the ACHR. Many scholars contend that the application of this doctrine should be carried out even if the domestic bodies that apply it have no constitutional power to do so. Others have a more restrictive interpretation and consider that domestic bodies would have to apply it to the extent of their power, according to their national constitutions. Apparently, the latter interpretation is gaining a wider support, which is desirable, because only this reading would be compatible with the principles of international law, and possibly accepted by all member States.